Victorino Rodríguez, Santiago Ramírez Dulanto, O. P. En, a centenario de su nacimiento (1891-1991) (Separata de La Ciencia Tomista, Salamanca, 1991) - Derisi, Octavio Nicolás (1991)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina